2019
DOI: 10.5606/archrheumatol.2020.7376
|View full text |Cite
|
Sign up to set email alerts
|

Association of Signal Transducer and Activator of Transcription 4 rs10181656 Polymorphism With Rheumatoid Arthritis and Systemic Sclerosis in Khuzestan Province in Southwestern Iran

Abstract: Objectives: This study aims to investigate the association of polymorphism rs10181656 (C>G) of signal transducer and activator of transcription 4 (STAT4) gene with rheumatoid arthritis (RA) and systemic sclerosis (SSc) in the southwest of Iran as well as the probable relationship between the polymorphism with clinical features and disease activity parameters in both diseases. Patients and methods: A total of 200 patients (120 with RA [21 males, 99 females; mean age 44.83 years; range, 16 to 75 years] and 80 wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…A meta-analysis showed that the STAT4 rs7574865 T allele was associated with RA in Europeans (OR = 1.300; 95% CI = 1.195-1.414; p < 0.001) [34]. Another study found a statistical association between rs10181656 and RA (p = 0.007) [35]. Furthermore, Hanan et al found that patients carrying the T allele of rs7574865 have a high risk of RA and SLE compared to healthy controls (p < 0.001) [36].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis showed that the STAT4 rs7574865 T allele was associated with RA in Europeans (OR = 1.300; 95% CI = 1.195-1.414; p < 0.001) [34]. Another study found a statistical association between rs10181656 and RA (p = 0.007) [35]. Furthermore, Hanan et al found that patients carrying the T allele of rs7574865 have a high risk of RA and SLE compared to healthy controls (p < 0.001) [36].…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies on the STAT4 rs10181656 SNP in the scientific literature databases. Scientific databases state that this SNP is associated with RA, SS, and SLE [20][21][22]. In a 2017-2018 study conducted in Iran, the STAT4 rs10181656 polymorphism was strongly associated with RA risk (p = 0.007), but no association was found with SS [21].…”
Section: Discussionmentioning
confidence: 99%
“…Scientific databases state that this SNP is associated with RA, SS, and SLE [20][21][22]. In a 2017-2018 study conducted in Iran, the STAT4 rs10181656 polymorphism was strongly associated with RA risk (p = 0.007), but no association was found with SS [21]. The STAT4 rs10181656 polymorphism has been associated with autoimmune diseases such as rheumatoid arthritis, systemic sclerosis, and systemic lupus erythematosus [21,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the scientific literature, the rs10181656, rs7574865, rs7601754 and rs10168266 polymorphisms influence the manifestation of various diseases, including autoimmune diseases. Associations have been found with Graves’ disease (GD) and Hashimoto’s thyroiditis (HT) as well as an increased risk of rheumatoid arthritis, systemic lupus erythematosus and type 1 diabetes [ 12 , 30 , 31 , 32 , 33 , 34 ]. However, no study has examined the impact of the occurrence of ON.…”
Section: Discussionmentioning
confidence: 99%